The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2016
DOI: 10.1002/eji.201646557
|View full text |Cite
|
Sign up to set email alerts
|

Macrophages and cardiac fibroblasts are the main producers of eotaxins and regulate eosinophil trafficking to the heart

Abstract: Cardiac manifestations are a major cause of morbidity and mortality in patients with eosinophil-associated diseases. Eosinophils are thought to play a pathogenic role in myocarditis. We investigated the pathways that recruit eosinophils to the heart using a model of eosinophilic myocarditis, in which experimental autoimmune myocarditis (EAM) is induced in IFNγ−/−IL-17A−/− mice. Two conditions are necessary for efficient eosinophil trafficking to the heart: high eotaxin (CCL11, CCL24) expression in the heart an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
55
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 57 publications
(59 citation statements)
references
References 56 publications
(63 reference statements)
4
55
0
Order By: Relevance
“…Flow cytometric evaluation of Siglec-F + eosinophils in blood and single cell digests of left ventricle (Figure 2a) revealed that, in parallel with clinical observations, there was a peripheral blood eosinopenia after experimental MI (p=0.003; Figure 2b). In keeping with previous studies, 12 Siglec-F + Ly6G int eosinophils were rarely found in uninjured hearts ( Figure 2c). However, eosinophils were recruited to the heart from Day 1 post-MI, and particularly to the infarct zone, where their numbers peaked at Day 4 post-MI, during infarct repair ( Figure 2c).…”
Section: Eosinophils Are Activated Following Experimental MI and Accusupporting
confidence: 93%
“…Flow cytometric evaluation of Siglec-F + eosinophils in blood and single cell digests of left ventricle (Figure 2a) revealed that, in parallel with clinical observations, there was a peripheral blood eosinopenia after experimental MI (p=0.003; Figure 2b). In keeping with previous studies, 12 Siglec-F + Ly6G int eosinophils were rarely found in uninjured hearts ( Figure 2c). However, eosinophils were recruited to the heart from Day 1 post-MI, and particularly to the infarct zone, where their numbers peaked at Day 4 post-MI, during infarct repair ( Figure 2c).…”
Section: Eosinophils Are Activated Following Experimental MI and Accusupporting
confidence: 93%
“…Thus, maintaining the right balance among different Th-directed cytokines is critical in preventing or limiting the progression of cardiac diseases to heart failure. We recently reported in a model of eosinophilic myocarditis that cardiac fibroblasts are potent producers of eotaxin 1 (CCL11), which is the main chemokine that regulates eosinophil trafficking to the heart [51]. In this study, we used the Sca-1 + cardiac fibroblasts from CCL2-mCherry reporter mice to demonstrate that the previous GM-CSF-and CCL2-expressing Sca-1 + cardiac fibroblasts are capable of switching to CCL11 producers after repolarization from Th17 to Th2 conditions.…”
Section: Discussionmentioning
confidence: 99%
“…Granulocyte macrophage colony-stimulating factor and IL-3 also promote eosinophil maturation from myeloid precursors 8. Diny et al 9 showed that cytokines from the Th2 pathway (IL-4 and IL-13) can activate fibroblasts and macrophages in cardiomyocytes, which will further elevate eotaxin (CCL11 and CCL24) expression. Therefore, CCR3 expressed in eosinophils will accumulate in cardiomyocytes, which leads to damage of heart tissue.…”
Section: Discussionmentioning
confidence: 99%